Gene expression profiles of microdissected pancreatic ductal adenocarcinoma - Grützmann, Robert; Foerder, Melanie; Alldinger, Ingo; Staub, Eike; Brümmendorf, Thomas; Röpcke, Stefan; Li, Xinzhong; Kristiansen, Glen; Jesenofsky, Ralf; Sipos, Bence; Löhr, J.-Matthias; Lüttges, Jutta; et al. (Virchows Archiv, 2003)
In a search for new molecular markers of pancreatic ductal adenocarcinoma (PDAC), we compared the gene expression profiles of seven pancreatic carcinomas and one carcinoma of the papilla Vateri with those of duct cells from three non-neoplastic pancreatic tissues. In addition, the human pancreatic duct cell line and five PDAC cell lines (AsPC-1, BxPC-3, Capan-1, Capan-2, HPAF) were examined. RNA was extracted from microdissected tissue or cultured cell lines and analysed using a custom-made Affymetrix Chip containing 3023 genes, of which 1000 were known to be tumour associated. Hierarchical clustering revealed 81 differentially expressed genes. Of all the genes, 26 were downregulated in PDAC and 14 were upregulated in PDAC. In PDAC cell lines versus normal pancreatic duct cells, 21 genes were downregulated and 20 were upregulated. Of these 81 differentially expressed genes, 15 represented human genes previously implicated in the tumourigenesis of PDAC. From the genes that were so far not known to be associated with PDAC tumorigenesis, we selected ADAM9 for further validation because of its distinct overexpression in tumour tissue. Using immunohistochemistry, the over-expressed gene, ADAM9, was present in 70% of the PDACs analysed. In conclusion, using microarray technology we were able to identify a set of genes whose aberrant expression was associated with PDAC and may be used to target the disease.
Gesehen am 24.05.2022